1981
DOI: 10.1161/01.res.49.1.150
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform electrophysiological properties and electrotonic interaction in hypertrophied rat myocardium.

Abstract: SUMMARY We studied the distribution and nature of the electrical changes associated with myocardial hypertrophy induced by renal hypertension in rats. Standard microelectrode techniqueB were used to study transmembrane action potentials recorded from endocardial, papillary muscle, and epicardial fibers from hypertrophied (HBP) and normal (SHAM) hearts. We also determined the effects of stimulation frequency on the action potentials recorded from these preparations. To assess whether altered intercellular elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 34 publications
(32 reference statements)
4
15
1
Order By: Relevance
“…Even though the resting potential and overshoot measured in this study are as large as those found by others in rat ventricular tissue (Payet et al, 1978;Gulch, 1980;Lazarus et al, 1980;Aronson, 1980;Keung and Aronson, 1981), they are on the low side for mammalian ventricular muscle. For example, the ca.…”
Section: Resting Potential and Overshootcontrasting
confidence: 57%
See 1 more Smart Citation
“…Even though the resting potential and overshoot measured in this study are as large as those found by others in rat ventricular tissue (Payet et al, 1978;Gulch, 1980;Lazarus et al, 1980;Aronson, 1980;Keung and Aronson, 1981), they are on the low side for mammalian ventricular muscle. For example, the ca.…”
Section: Resting Potential and Overshootcontrasting
confidence: 57%
“…As expected from Figure 2, the APD25 and APD75 of type III action potentials (14.5 ± 1.9 and 46.0 ± 4.1 msec) were significantly longer ( P < 0.01-0.001) than those of type II (7.4 ± 1.1 and 38.2 ±-6.7 msec) which, in turn, were longer ( P < 0.001) than those of type I (3.1 ± 1.0 and 21.5 ± 3.6 msec). The other significant difference (P < 0.05-0.001) between the three types of action potentials was that the amplitude of type III Gulch (1980), and Keung and Aronson (1981), found that the configuration of the action potential in rat ventricle was not homogeneous. Thus, one explanation for the presence of several populations of action potentials in the isolated myocytes is that there are also several populations in the intact tissue.…”
Section: Three Types Of Stable Action Potentialsmentioning
confidence: 92%
“…However, stresses induced in the rat by renal hypertension which produce hypertrophy increase cell size more in the epicardial layers, and resulting transmural gradients become evident in mitochondrial-to-myofibrillar ratio and in the Tsystem surface density (Anversa et al, 1978). Regional regulation of electrical properties in the epicardial myocytes has also been seen in the rat during hypertrophy (Keung and Aronson, 1981).…”
Section: Discussionmentioning
confidence: 88%
“…The electrophysiological changes underlying spontaneous ectopic activity in LVH are not well understood, but hypertrophied myocardium clearly represents a complex substrate for arrhythmic disturbance. Prolongation of the cardiac action potential has been reported in experimental animal models, and abnormalities in individual currents, including I CaL , I Na , and I to , have been described in hypertrophied cardiac myocytes (Keung and Aronson, 1981;Keung, 1989;Ryder et al, 1993;Yokoshiki et al, 1997). Increased interstitial fibrosis, a universal feature of hypertensive LVH (Weber, 2000), may create zones of altered electrical conductance.…”
Section: B Experimental Ischemia/reperfusion Injury In Left Ventricumentioning
confidence: 99%